Bacteroides plebeius sp. nov. and Bacteroides coprocola sp. nov., isolated from human faeces - Maki Kitahara; Mitsuo Sakamoto; Masako Ike; Shinji Sakata; Yoshimi Benno (2005)
Nine strains of Gram-negative, anaerobic rod were isolated from human faeces. Based on phylogenetic analysis and specific phenotypic characteristics, these strains were included within the Bacteroides cluster and were divided into two clusters. Strains from the two clusters showed 16S rRNA gene sequence similarities of 90.4 and 92.7% to the nearest recognized species, Bacteroides vulgatus. The strains also formed two clusters exhibiting a 16S rRNA gene sequence divergence of approximately 6%. DNA-DNA hybridization studies confirmed that the two novel strain clusters were distinct from each other. Based on the phenotypic and phylogenetic findings, two novel species, Bacteroides plebeius sp. nov. and Bacteroides coprocola sp. nov., are proposed, each representing one of the two strain clusters. The DNA G+C content of the type strains were 43.9 mol% for B. plebeius (M12(T)=JCM 12973(T)=DSM 17135(T)) and 42.4 mol% for B. coprocola (M16(T)=JCM 12979(T)=DSM 17136(T)).